ORTHOPEDONEUROSURGICAL TREATMENT FOR PRIMARY AND METASTATIC VERTETAL TUMORS WITH COMPRESSED SPINAL CORD - Fazilov, Shukhratulla (Medical science of Uzbekistan, 2022)
Incomplete information about the localization, extent and nature of the tumor in spinal complications does not allow performing complex operations with an anterior approach, therefore, in such situations, most surgeons consider it possible to limit the surgical intervention to decompressive laminectomy with posterior fusion, in the most difficult cases, without spinal fixation. The aim of the work is to study the effectiveness of decompressive-stabilizing operations using anterior and posterior approaches in patients with tumors of the vertebral bodies complicated by spinal cord compression. Materials and methods. We examined 55 patients hospitalized for urgent indications with severe pain syndrome, which was difficult to stop with narcotic analgesics, and spinal disorders in the form of gross paresis (38) and paralysis (17, of which 15 in combination with dysfunctions of the pelvic organs) caused by a tumor in the cervical (35) and thoracic (20) spine. Results and discussion. Decompressive-stabilizing operations in patients with tumors of the vertebral bodies complicated by compression of the spinal cord, limiting diagnostic possibilities, prevented the progression of spinal complications and secondary compression of the spinal cord in 39 people. Surgical treatment did not significantly affect life expectancy, but to a large extent affected its quality. The most effective operations are anterior access. In our opinion, their best results are due to the possibility of removing tumor masses with complete decompression of the spinal cord and strong stabilization of the spine.